Clinical trajectory and outcomes of patients with heart failure with preserved ejection fraction with normal or indeterminate diastolic function. (3rd October 2022) - Oeun, B; Hikoso, S; Nakatani, D; Okada, K; Dohi, T; Sotomi, Y; Kida, H; Sunaga, A; Sato, T; Seo, M; Yano, M; Hayashi, T; et al.
Abstract: Background: Heart failure (HF) with preserved ejection fraction (HFpEF) is a chronic and progressive disease, but limited therapeutic strategies are currently available. Although left ventricular diastolic dysfunction (DD) is a prominent mechanism of HFpEF, a certain number of patients with HFpEF have a normal diastolic function (ND) or indeterminate diastolic function (ID). With the progressive nature of HFpEF, diastolic function may change over time. However, the change of diastolic function, its predictor and prognosis in patients with clinically established HFpEF remains unknown. Purpose: To investigate the clinical trajectory and outcomes of patients with HFpEF with ND or ID and to identify factors associated with progression from ND or ID at discharge to DD at 1-year follow-up. Methods: Using data from a prospective multicenter observational study of patients with HFpEF, we extracted 289 patients with HFpEF with ND or ID at discharge who had echocardiographic data at 1-year follow-up for the re-evaluation of diastolic function. Diastolic function was assessed according to the 2016 American Society of Echocardiography recommendations. Patients were classified according to the absence or presence of progression from ND or ID to DD at 1 year. The primary endpoint was a composite of all-cause death and HF rehospitalization. Results: Median age was 81 years, and 138 (47.8%) patients were female. At 1 year, 107 (37%) patients progressed to DD. During a median follow-up of 709 days, the composite endpoint occurred in 90 (31.1%) patients. Compared to patients without progression to DD, those with progression to DD had a significantly higher cumulative incidence rate of the composite endpoint (incidence rate: 11.7/100 person-year versus 23.3/100 person-year, P<0.001). Progression to DD (adjusted HR: 2.014, 95% CI: 1.239–3.273, P=0.005) was independently associated with the composite endpoint. Age (adjusted OR: 1.046, 95% CI: 1.008–1.087, P=0.018), body mass index (BMI) (adjusted OR: 1.107, 95% CI: 1.029–1.192, P=0.006), and serum albumin (adjusted OR: 0.459, 95% CI: 0.216–0.974, P=0.042) were independently associated with progression from ND or ID to DD at 1 year. Conclusion: More than one-third of patients with HFpEF with ND or ID progressed to DD at 1 year and had poor clinical outcomes. Age, BMI, and serum albumin were independently associated with this progression. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by grants from Japan Society for the Promotion of Science KAKENHI (No. JP 17K09496) and Japan Agency for Medical Research and Development (No. JP16lk1010013).